Study on the Effect of Cyanide Concentration on Gold Leaching Recovery in Ore at PT Indo Muro Kencana - Putri GF, Frideni Yushandiana; Karimah, Armitha Lisanul; ., Sulaeman (Program studi Teknik Kimia UNS, 2023)
ABSTRACT. Indonesia is a country that has abundant natural resources, including non-renewable natural resources such as various types of metals, natural gas, petroleum and others. Besides that, Indonesia also has an important role in supplying the world's gold raw materials. Therefore, it is necessary to develop technology and science in the mining industry, especially gold to increase process optimization and increase the added value of the mining products themselves. One of the gold extraction processes can be carried out hydrometallurgically using the cyanidation method using agitator leach, as was done at PT Indo Muro Kencana. Process optimization is carried out with various test work, such as leaching tests, by varying the operating parameters of the leaching. The variations of parameters used in this study are the cyanide concentrations at 600 ppm, 700 ppm, and 800 ppm. The results of the analysis show that the optimal cyanide concentration for leaching of PT Indo Muro Kencana's gold ore is 600 ppm by controlling the Rate rate control.Keywords:Cyanidation, Gold, Leaching, Extraction.